2005
DOI: 10.1111/j.1365-2559.2005.01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis and pigmented villonodular synovitis: comparative analysis of cell polyploidy, cell cycle phases and expression of macrophage and fibroblast markers in proliferating synovial cells

Abstract: In spite of their histologically homogeneous appearance, proliferating synovial cells display a heterogeneous immunophenotype in both RA and PVNS, indicating functional properties of both macrophages and fibroblasts. Aneuploidy seems to be a special feature of diffuse PVNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 15 publications
2
26
0
2
Order By: Relevance
“…The highest transfection rates were achieved in synoviocytes and were attributed to their macrophage-like characteristics [63][64][65]. Consistently, we previously showed that more than 80% of the synoviocytes took up superparamagnetic nanoparticles within 24 h [54].…”
Section: Article In Presssupporting
confidence: 75%
“…The highest transfection rates were achieved in synoviocytes and were attributed to their macrophage-like characteristics [63][64][65]. Consistently, we previously showed that more than 80% of the synoviocytes took up superparamagnetic nanoparticles within 24 h [54].…”
Section: Article In Presssupporting
confidence: 75%
“…Previous studies demonstrated that proliferating cells in PVNS are mainly composed of synovial cells with features of both macrophages and fibroblasts (43). A temporally limited proliferation of these cells can also be seen in the active phase of RA.…”
Section: Discussionmentioning
confidence: 91%
“…In RA and other arthritides, modest proliferation has been described, at least in some reports, in a range of cell types, including macrophages (24,29,30). In early human atheroma, the predominant proliferating cell type is the macrophage lineage foam cell (26) and, during an inflammatory response in the brain, microglial proliferation is an early component of the activation of macrophage lineage foam cells by agents such as macrophage-CSF (M-CSF) (also known as CSF-1) and granulocyte-macrophage CSF (GM-CSF) (25).…”
Section: Mechanisms Controlling Ra Synovial Macrophage Numbersmentioning
confidence: 99%